Non-Holonomic Robot Navigation Path Planning Using Fuzzy - Steepest Ascent Hill Climb - Gustami, Heri; Mawengkang, Herman; Budhiarti, Erna (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Robot navigation is determination position as well as direction movement in a trip . Planning track is matter most important in the world of mobile robots. in short , determination track will produce dynasty that can traversed (feasible) with availability information that has there is that is map robotic environment . modelling environment map is step first for determine path planning. on the contrary for environment that doesn't known , modeling will done with the information obtained from the sensors on the robot . on the environment actually , noise and limitations accuracy from the sensor leads to the most basic problem in modeling, that is accuracy , and speed , where influence system navigation live in real-time. For resolve matter the needed the existence of a Fuzzy Description Environment which consists of over the fuzzy model of information obtained in the environment around robots. of these models will Becomes base reference path planner that is used reference to path planning. From the map environment modeling will processed by Steepest Ascent Hill Climb so produce track going to point end . From the results program simulation is obtained waypoints with _ distance shortest that is 363.2724 units distance